Relationship Between Quality of Life and Level of Physical Activity and Family Well-Being - Olena Andrieieva; Dmytro Maltsev; Vitalii Kashuba; Myroslav Dutchak; Dmytro Ratnikov; Igor Grygus; Natalia Byshevets; Inna Horodinska (OVS LLC, 2022)
Study purpose. The objective of the study was to assess the relationship between quality of life and physical activity level and family well-being. Materials and Methods. The International Physical Activity Questionnaire (IPAQ) was used to assess parental physical activity. The quality of life was assessed with the Short Form (SF-36) Health Survey Questionnaire. The data obtained were processed using cluster and correlation analysis, and descriptive statistics. The study involved 106 young adults (married couples), who were parents of preschool and primary school-aged children. Results. An assessment of parental physical activity showed that 62.3% of the respondents had a low level of physical activity and 37.7% had a moderate level, whereas no individuals with a high level of physical activity were found. Families with children were divided into clusters with the k-means method according to the level of physical activity: Cluster 1 included families with a low level of physical activity; and Cluster 2 included the families with a moderate level of physical activity. The results of the study confirmed the relationship between the quality of life and the level of physical activity and family well-being. It was found that all the quality of life components of the study participants with a moderate level of physical activity are significantly higher (р<0.05) than those of the participants with a low level of physical activity. Correlation analysis of family well-being and quality of life indicators revealed significant relationships (p<0.05) between physical functioning, physical role functioning, vitality, and mental health. Conclusions. The direct statistically significant relationship between family well-being score and quality of life components of the respondents was demonstrated.